The Role of Renal Replacement Therapy in the Management of Pharmacologic Poisonings - Aibek E. Mirrakhimov; Aram Barbaryan; Adam Gray; Taha Ayach (International Journal of Nephrology)
Pharmacologic toxicities are common and range from mild to life-threatening. The aim of this study is to review and update the data on the role of renal replacement therapy (RRT) in the management of various pharmacologic poisonings. We aim to provide a focused review on the role of RRT in the management of pharmacological toxicities. Relevant publications were searched in MEDLINE with the following search terms alone or in combination: pharmacologic toxicity, hemodialysis, hemofiltration, renal replacement therapy, toxicology, poisonings, critical illness, and intensive care. The studies showed that a pharmacologic substance should meet several prerequisites to be deemed dialyzable. These variables include having a low molecular weight (<500 Da) and low degree of protein binding (<80%), being water-soluble, and having a low volume of distribution (<1 L/kg). RRT should be strongly considered in critically ill patients presenting with toxic alcohol ingestion, salicylate overdose, severe valproic acid toxicity, metformin overdose, and lithium poisoning. The role of RRT in other pharmacologic toxicities is less certain and should be considered on a case-by-case basis.